Effect of skull contours on dose calculations in Gamma Knife Perfexion stereotactic radiosurgery. (6th March 2014) - Nakazawa, Hisato; Komori, Masataka; Mori, Yoshimasa; Hagiwara, Masahiro; Shibamoto, Yuta; Tsugawa, Takahiko; Hashizume, Chisa; Kobayashi, Tatsuya
Abstract : In treatment planning of Leksell Gamma Knife (LGK) radiosurgery, the skull geometry defined by generally dedicated scalar measurement has a crucial effect on dose calculation. The LGK Perfexion (PFX) unit is equipped with a cone‐shaped collimator divided into eight sectors, and its configuration is entirely different from previous model C. Beam delivery on the PFX is made by a combination of eight sectors, but it is also mechanically available from one sector with the remaining seven blocked. Hence the treatment time using one sector is more likely to be affected by discrepancies in the skull shape than that of all sectors. In addition, the latest version (Ver. 10.1.1) of the treatment planning system Leksell GammaPlan (LGP) includes a new function to directly generate head surface contouring from computed tomography (CT) images in conjunction with the Leksell skull frame. This paper evaluates change of treatment time induced by different skull models. A simple simulation using a uniform skull radius of 80 mm and anthropomorphic phantom was implemented in LGP to find the trend between dose and skull measuring error. To evaluate the clinical effect, we performed an interobserver comparison of ruler measurement for 41 patients, and compared instrumental and CT‐based contours for 23 patients. In the phantom simulation, treatment time errors were less than 2% when the difference was within 3 mm. In the clinical cases, the variability of treatment time induced by the differences in interobserver measurements was less than 0. 91%, on average. Additionally the difference between measured and CT‐based contours was good, with a difference of − 0.16 % ± 0.66 % (mean ±1 standard deviation) on average and a maximum of 3.4%. Although the skull model created from CT images reduced the dosimetric uncertainty caused by different measurers, these results showed that even manual skull measurement could reproduce the skull shape close to that of a patient's head within an acceptable range. PACS number: 87.53.Ly